Synthesis of the sedum and related alkaloids: A personal perspective. Issue 7 (14th February 2018) - Bates, Roderick W.
Graphical abstract: Highlights: Synthesis of the sedum and related alkaloids. Recent significant developments. Inventive contributions to the field. Abstract: Significant recent contributions to the synthesis of the sedum alkaloids are discussed. Related compounds, such as pinidinol, porantheridine, dumetorine and the tetraponerines are also included. The syntheses are categorised according to the key motif or chemistry employed: isoxazolidines, metathesis, asymmetric aza-Michael, heterocycle lithiation, organocatalysis, aromatic heterocycles and chiral imines.